2021
DOI: 10.1111/jocd.14391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen in malignant melanoma

Abstract: The ultimate effect of estrogen signaling on a tissue largely depends on the relative expression of estrogen receptors (ER) α and β. The latter are members of the nuclear receptor family of transcription factors. They are involved in the formation of a multi-protein complex and can form homo/heterodimers that upon activation, they move into the nucleus to bind with their coregulatory proteins. Through the binding to specific ER response element regions, they control the transcription of specific target genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
1
8
0
Order By: Relevance
“…Immunohistochemical observations from 38 patients with melanoma confirmed that ERα expression was absent malignant melanoma ( 297 ). Traditionally, ERα was thought to promote the growth of melanoma cells ( 298 ). Tian et al.…”
Section: Ers In the Manifestation Of Diseasesmentioning
confidence: 99%
“…Immunohistochemical observations from 38 patients with melanoma confirmed that ERα expression was absent malignant melanoma ( 297 ). Traditionally, ERα was thought to promote the growth of melanoma cells ( 298 ). Tian et al.…”
Section: Ers In the Manifestation Of Diseasesmentioning
confidence: 99%
“…ERα enhances DNA transcription, while ERβ inhibits it. ERα plays a role in tumorigenesis by stimulating cell proliferation, while ERβ seems to have a significant antiproliferative activity [4,12]. Moreover, steroid hormones elicit 'nongenomic pathway' activation by inducing the activation of the RAS/BRAF/MEK axis, which has a key role in CM development and treatment [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…ERα has a relevant role in the cross-talk of the steroid driven nongenomic pathway and MAPK activation as showed in ERα KO mice, where it was absent, suggesting a key interaction between these two pathways [4]. Furthermore, G protein-coupled estrogen receptor (GPER), with its specific agonists G1 and 17β-estradiol, promotes melanogenesis through the increase of cAMP levels and final activation of the microphthalmia-associated transcription factor (MITF) [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…Initiation and growth of these tumor types are well known to be driven by nuclear hormone receptors, such as ER, AR, and PR, and therefore these effects on tumor development are likely to be cell‐autonomous. In melanoma as well, it has been suggested that sex‐specific cellular expression of the ERs contributes to tumor development 40 . This might explain the sex steroid hormone‐dependent effects within cohorts of cisgender men or women.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma as well, it has been suggested that sex-specific cellular expression of the ERs contributes to tumor development. 40 This might explain the sex steroid hormone-dependent effects within cohorts of cisgender men or women. However, the ER expression levels in a transgender individual might not be altered by GAHT per se, which could be a mechanistic explanation for the observed lack of effect of GAHT on melanoma development.…”
Section: Discussionmentioning
confidence: 99%